Spatiotemporal Variation Characteristics and Driving Factors of Nitrogen Use Efficiency of Wheat–Rice Rotation Systems in the Taihu Lake Region - Lu, Xiaosong; Ma, Lixia; Yu, Dongsheng; Chen, Yang; Wang, Xin (Frontiers in Soil Science, 2021)
China is implementing the national strategy “fertilizer reduction with efficiency increase’’ to solve the serious ecological problems caused by excessive fertilization. However, the effects of nitrogen fertilizer reduction on soil fertility, and their integrated effect on nitrogen use efficiency (NUE) of rice-wheat rotation systems in Taihu Lake region are not fully understood. In this study, test fields with different soil fertility qualities were selected in typical rice-wheat areas in Taihu Lake region to perform a 2-year rice-wheat N fertilizer effect test to obtain the comprehensive quantitative relationship among cultivated land fertility index (IFI), nitrogen application level (NA) and NUE. Through the investigation and spatial analysis of NA and IFI in the study area in 2003 and 2017, the spatial and temporal variation characteristics of NA and IFI in the study area in the past 15-year period were obtained, and this information was spatially coupled with the comprehensive quantitative relationship model of NUE to reveal the variation characteristics and driving factors of NUE in the study area. The result showed that the wheat and rice NA in the study area in 2017 increased by 35.5% and 8.4%, respectively, compared with 2003. Due to excessive fertilization, the soil nitrogen, phosphorus and potassium content of cultivated land in the study area in 2017 was greater than that in 2003, especially soil available phosphorus and potassium contents, whereas soil organic matter content was reduced. The cultivated land IFI of the study area as a whole increased by 7.2% in the 15-year period. The NUE of rice and wheat rotation increased by 5.8% in 2017 compared with that of 2003 due to the improvement in crop varieties and N fertilizer yield benefits. In the context of soil fertility improvement, N fertilizer reduction with increased efficiency can only be achieved by reducing the N fertilizer application according to the appropriate amount of nitrogen applied to rice and wheat. It is hoped that this study provides a new method for precise fertilization and N fertilizer reduction with increased efficiency in the study area and other agricultural areas.